2022
DOI: 10.1001/jamapsychiatry.2022.3541
|View full text |Cite
|
Sign up to set email alerts
|

A Positron Emission Tomography Study of Dopamine Transporter Density in Patients With Bipolar Disorder With Current Mania and Those With Recently Remitted Mania

Abstract: ImportanceAlthough dopamine is implicated in the pathophysiology of bipolar disorder (BD), the precise alterations in the dopaminergic system remain unknown.ObjectiveTo assess dopamine transporter (DAT) density in the striatum in patients with BD with current and recently remitted mania in comparison to healthy control individuals and its correlation with severity of manic symptoms.Design, Setting, and ParticipantsThis cross-sectional study conducted in a tertiary care referral center for mood disorders in Van… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…They considered striatal dopaminergic D2/D3 receptor availability, explaining elevated dopaminergic neurotransmission in mania, and an increase in striatal dopamine transporter (DAT), elucidating lowered dopaminergic function in depression. The latter finding was corroborated in a recent study by Yatham et al [ 89 ], showing reduced DAT in the right putamen and nucleus accumbens during an acute manic episode, suggesting dopaminergic overactivity. Therefore, the therapeutic action in mania, as well as the prevention of manic episodes in bipolar disorder, can be connected with the anti-dopaminergic activity, mainly by blocking D2 receptors, which manifests in all three generations of antipsychotic drugs.…”
Section: Mechanism Of Therapeutic Action Of Antipsychotic Drugs In Mo...supporting
confidence: 82%
“…They considered striatal dopaminergic D2/D3 receptor availability, explaining elevated dopaminergic neurotransmission in mania, and an increase in striatal dopamine transporter (DAT), elucidating lowered dopaminergic function in depression. The latter finding was corroborated in a recent study by Yatham et al [ 89 ], showing reduced DAT in the right putamen and nucleus accumbens during an acute manic episode, suggesting dopaminergic overactivity. Therefore, the therapeutic action in mania, as well as the prevention of manic episodes in bipolar disorder, can be connected with the anti-dopaminergic activity, mainly by blocking D2 receptors, which manifests in all three generations of antipsychotic drugs.…”
Section: Mechanism Of Therapeutic Action Of Antipsychotic Drugs In Mo...supporting
confidence: 82%
“…The dopamine hypothesis of bipolar disorder (BD) has been proposed based on the similarity between behavioral changes induced by amphetamine administration and manic symptoms, as well as the effects of antidopaminergic medications on manic symptoms. Although dopaminergic neuroimaging studies have revealed various abnormalities in BD, there are also many inconsistencies in the findings across studies [36,37]. Some studies have reported that striatal dopamine transporter (DAT) activity is decreased only in the manic state of BD [36,37], while others have reported a decrease also in euthymia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Although dopaminergic neuroimaging studies have revealed various abnormalities in BD, there are also many inconsistencies in the findings across studies [36,37]. Some studies have reported that striatal dopamine transporter (DAT) activity is decreased only in the manic state of BD [36,37], while others have reported a decrease also in euthymia [20]. The present study found that most BD patients with parkinsonism had reduced striatal DAT activity, and there was a trend of correlation between striatal DAT activity and the severity of parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…A significant effect on VGSCs is also reported for the bias-ligand aripiprazole [ 568 ]. Concerning the dopaminergic presynaptic mechanism, DAT has also been implicated for its potential involvement in antipsychotics’ response despite the fact that its role in schizophrenia pathophysiology is still elusive partly due to methodological limitations both at clinical and preclinical levels [ 5 , 569 , 570 , 571 ]. Beyond intracellular dopamine D2-directly mediated signaling, dopamine-dependent trans-synaptic mechanisms have emerged, unveiling antipsychotics’ impact on the expression and functions of molecules belonging to different neurotransmitter systems.…”
Section: Discussionmentioning
confidence: 99%